Evaluation of five promoters for use in transformation of oil palm (Elaeis guineensis Jacq.) - Chowdhury, M.K.U.; A. Parveez, Ghulam Kadir; M. Saleh, Norihan (Springer-Verlag, 1997)
The efficiency of GUS (β-Glucuronidase) gene expression in embryogenic callus and young leaflets of mature and seedling palm after microprojectile bombardment with five constructs (pEmuGN, pAHC25, pAct1-F4, pGH24 and pBARGUS) was evaluated to identify the most suitable promoter(s) to use in transformation attempts in oil palm Expression of the GUS gene driven by the Emu, Ubi1, Act1, 35S or Adh1 was assayed, both histochemically and fluorometrically, from a total of 200 plates of tissues in eight independent experiments two days after bombardment A completely randomized experimental design was used for each experiment, and the data analysed by ANOVA and Duncan's Multiple Range Test. The expression level of GUS driven by the Emu or Ubi1 promoters was significantly higher than that of the Act1, 35S and Adh1 promoters in many experiments, and that of the Adh1 was significantly lower than those of the other four promoters. Both histochemical and fluorometric data indicate that in embryogenic callus, the expression of the Emu promoter was higher than that of the Ubi1 whereas in young leaflets from mature palm the Ubi1 expression was stronger. The performances of the five promoters were also tested in tobacco callus using a fluorometric GUS assay. The activity of the 35S promoter was highest, and significantly different from that of all the other promoters except the Emu, and that of the Act1 promoter was lowest. These results indicate that either the Ubi1 or Emu promoter should facilitate the expression of desired genes in oil palm and aid in development of an efficient stable transformation system.